Alternating or compensating? An experiment on the repeated sequential best shot game - Lisa Bruttel; Werner Güth (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2013)
In the two-person sequential best shot game, first player 1 contributes to a public good and then player 2 is informed about this choice before contributing. The payoff from the public good is the same for both players and depends only on the maximal contribution. Efficient voluntary cooperation in the repeated best shot game therefore requires that only one player should contribute in a given round. To provide better chances for such cooperation, we enrich the sequential best shot base game by a third stage allowing the party with the lower contribution to transfer some of its periodic gain to the other party. Participants easily establish cooperation in the finitely repeated game. When cooperation evolves, it mostly takes the form of labor division with one participant constantly contributing and the other constantly compensating. However, in a treatment in which compensation is not possible, (more or less symmetric) alternating occurs frequently and turns out to be almost as efficient as labor division.
Keywords: C71; C73; C91; 330; best shot game; coordination; experiment; transfer